The impact of artificial intelligence-assisted teaching on enhancing physical education quality in secondary vocational schools - Wu, Zhanghua; Buaduang, Rawi; White, Alan Robert; Darodjat, Tubagus; Rattanapun, Supot (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates the effects of the sports prescription teaching model and artificial intelligence (AI)-assisted teaching on the intelligent teaching process and the overall quality of physical education (PE) instruction in secondary vocational schools. It further examines the mediating role of the intelligent teaching process in enhancing teaching outcomes. A quantitative research design was employed, with data collected from 414 students across five secondary vocational schools in Nanning, China. The study used descriptive statistics, validity and reliability testing, correlation analysis, and multiple regression analysis to examine the relationships among key variables: sports prescription teaching, AI-assisted teaching, intelligent teaching processes, and PE teaching quality. The intelligent teaching process significantly enhanced PE teaching quality, particularly in personalized training (M = 4.35), skill acquisition (M = 4.33), and classroom interaction and enjoyment (M = 4.31). Key statistical findings include: (1) the sports prescription teaching model significantly predicted intelligent teaching (β = 0.893, R² = 0.798); (2) AI-assisted teaching had a strong positive effect on intelligent teaching (β = 0.900, R² = 0.810); (3) the intelligent teaching process significantly mediated the influence of both teaching models on teaching quality (β = 0.880, R² = 0.798); (4) intelligent teaching enhanced the effectiveness of the sports prescription model (β = 0.866, R² = 0.806); (5) and it amplified the impact of AI-assisted teaching (β = 0.874, R² = 0.810). The intelligent teaching process serves as a crucial mediating factor that enhances the effectiveness of both the sports prescription teaching model and AI-assisted teaching in vocational physical education settings. These findings support the integration of AI technologies and evidence-based instructional models such as sports prescriptions into vocational education. Educators and policymakers are encouraged to adopt intelligent teaching strategies to foster personalized, engaging, and health-promoting PE experiences that improve learning outcomes for vocational students.